(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the problems of educational quality arising in the process of introducing digital technologies into the modern education system and their didactic foundations. The pedagogical possibilities of forming a digital educational environment in higher education institutions, the effective use of information and communication technologies in the educational process, and improving the quality of education are highlighted. The importance of didactic principles, methods, and tools in integrating digital technologies into the educational process is also substantiated. The study revealed that the effective use of digital technologies contributes to the interactivity of the educational process, increasing students’ independent educational activities, and motivation for learning.